(untitled) (Al-Academy, 2021)
This research aims to identify the economic design techniques and materials that can be used in the implementation of cosmetic supplements to the spaces of the dwelling. The research relied on the descriptive and analytical approach by describing and analyzing models of design techniques and materials that can be used in the production of cosmetic supplements in the interior spaces of the dwelling.The results of the research concluded that the beautification of the spaces of the dwelling is one of the necessary and important pieces to add aesthetic touches to the internal spaces, and that the use of economic design techniques and materials contributes to the implementation of many pieces of complementary beautification of the internal spaces of the dwelling at a simple cost and not exaggerated, and the research recommendations were the necessity Urging training centers to hold training courses and workshops for women in the field of home beautification and providing them with simple and economical techniques aimed at developing their awareness of home beautification, and stressing the need to train students in the courses related to home management or family education on how to use design techniques and materials and employ them in an economic way .